Comparison of the Effectiveness of Solution-Focused Brief Therapy and Compassion-Focused Therapy on Interpersonal Relationships between Couples with Depression - Leili Ghari Saadati; Shohreh Ghorban Shiroudi; Javad Khalatbari (Hamadan University of Medical Sciences, 2022)
Background and Objective: Depression is a multifactorial psychological disorder that is caused by various factors, such as personality, cognition, or interpersonal relationships. In people with depression, the level of interpersonal communication is highly low. Therefore, this study aimed to compare the effectiveness of Solution-Focused Brief Therapy and Compassion-Focused Therapy on interpersonal communication between couples with depression. Materials and Methods: This quasi-experimental study was conducted based on a pretest-posttest design with a control group and follow-up. The statistical population of the study consisted of couples with depression referring to clinics in District 1 of Mashhad, Iran, among whom, 45 samples were included in the study using inclusion criteria and a purposive random sampling method. Subsequently, they were randomly assigned to the groups of Solution-Focused Brief Therapy, Compassion-Focused Therapy, and the control group (n=15 pairs each). The first intervention group participated in six 90-120-minute sessions per week for the Solution-Focused Brief Therapy training program and the second intervention group took part in eight -120-minute sessions weekly for the Compassion-Focused Therapy training program. No intervention was performed for the control group. The tool employed to collect the required data was Matson's Evaluation of Social Skills with Youngsters. The research data were analyzed in SPSS software (version 24) using analysis of covariance, Lamtrix post hoc test, Scheffe post hoc test, and analysis of variance. The significance level was analyzed as α = 0.05. Results: Descriptive findings showed that the mean scores of the variable interpersonal relationships in the pre-test, post-test, and follow-up stages were obtained respectively at 44.32±4.68, 45.51±4.50, and 42.32±4.12 for the control group; 45.53±4.77, 59.32±5.93, and 67.18±6.75 for the Solution-Focused Brief Therapy group; and 43.19±4.62, 63.74±6.04, and 73.22±7.39 for the Compassion-Focused Therapy group. The results of comparing the groups showed that Solution-Focused Brief Therapy and Compassion-Focused Therapy had significant effects on the interpersonal relationships between couples with depression (P<0.05). Moreover, there was a significant difference between the effectiveness of Solution-Focused Brief Therapy and Compassion-Focused Therapy on the interpersonal communications between couples with depression (P<0.05). Conclusion: The results showed that short-term Solution-Focused Brief Therapy and Compassion-Focused Therapy were effective on the interpersonal relationships of couples with depression. Therefore, based on the results of the present study, it is suggested that family counselors and couple therapists use the methods and practices of Solution-Focused Brief Therapy and Compassion-Focused Therapy to improve the level of interpersonal relationships between depressed couples.